Housing equity withdrawal: uses, risks, and barriers to alternative mechanisms in later life - Ong, Rachel; Jefferson, Therese; Wood, G.; Haffner, M.; Austen, Siobhan (Australian Housing and Urban Research Institute, 2013)
This project uncovers the uses, risks of and barriers to housing equity withdrawal (HEW) by older home owners aged 45 years and over via three alternative mechanisms: in situ mortgage equity withdrawal (MEW), downsizing and selling up. Its overall objective is to provide an evidence base for policies and programs aimed at maximising the availability and quality of information to support Australians in their decision-making over the use of housing wealth in later life.